The semantics and contextualized use of the Present Perfect in modern American English: A corpus-driven study - Zolotarev, Mikhail Vladimirovich; Popp, Arina Vladimirovna (Известия Саратовского университета. Новая серия. Серия Филология: Журналистика, 2023)
The article identifies the main ways in which the Present Perfect meanings are expressed in the oral speech of the US citizens speaking American English. The necessity to study in detail how the Present Perfect functions in modern American English is attributed to the emerging reports emphasizing the existing functional instability of these forms in the speech of Americans. This tendency shows that the Present Perfect loses its ability to express traditional perfect meanings. Therefore, the aim of the study is twofold: to apply the methods of corpus linguistics in order to confirm that the semantics of the perfect and preterite forms tend to merge in modern American English, as well as to collect and describe the contexts in which the preterite substitutes the Present Perfect forms in their traditional meanings. We created a corpus of oral texts and collected the data reflecting the frequency of the perfect and preterite forms found in the speech of the respondents. Based on the comparative analysis, we carried out the research determining the percentage ratio of the perfect meanings expressed by the preterite forms. It was found that today in the oral speech of the US women aged 18–25 the preterite verb forms substitute the perfect verb forms in their traditional meanings in almost a third of the contexts. At the same time, the preterite replaces the perfect only in its ‘stative’ and ‘existential’ meanings. The findings confirm the hypothesis that the Present Perfect evolves in American English in accordance with the scenario of “arrested” grammaticalization where the semantics of the perfect and the preterite merge.